A Pseudomonas aeruginosa Antimicrobial Affects the Biogeography but Not Fitness of Staphylococcus aureus during Coculture - Juan P. Barraza (American Society for Microbiology, 2021)
ABSTRACT Pseudomonas aeruginosa and Staphylococcus aureus are two of the most common coinfecting bacteria in human infections, including the cystic fibrosis (CF) lung. There is emerging evidence that coinfection with these microbes enhances disease severity and antimicrobial tolerance through direct interactions. However, one of the challenges to studying microbial interactions relevant to human infection is the lack of experimental models with the versatility to investigate complex interaction dynamics while maintaining biological relevance. Here, we developed a model based on an in vitro medium that mimics human CF lung secretions (synthetic CF sputum medium [SCFM2]) and allows time-resolved assessment of fitness and community spatial structure at the micrometer scale. Our results reveal that P. aeruginosa and S. aureus coexist as spatially structured communities in SCFM2 under static growth conditions, with S. aureus enriched at a distance of 3.5 μm from P. aeruginosa. Multispecies aggregates were rare, and aggregate (biofilm) sizes resembled those in human CF sputum. Elimination of P. aeruginosa’s ability to produce the antistaphylococcal small molecule HQNO (2-heptyl-4-hydroxyquinoline N-oxide) had no effect on bacterial fitness but altered the spatial structure of the community by increasing the distance of S. aureus from P. aeruginosa to 7.6 μm. Lastly, we show that coculture with P. aeruginosa sensitizes S. aureus to killing by the antibiotic tobramycin compared to monoculture growth despite HQNO enhancing tolerance during coculture. Our findings reveal that SCFM2 is a powerful model for studying P. aeruginosa and S. aureus and that HQNO alters S. aureus biogeography and antibiotic susceptibility without affecting fitness. IMPORTANCE Many human infections result from the action of multispecies bacterial communities. Within these communities, bacteria have been proposed to directly interact via physical and chemical means, resulting in increased disease and antimicrobial tolerance. One of the challenges to studying multispecies infections is the lack of robust, infection-relevant model systems with the ability to study these interactions through time with micrometer-scale precision. Here, we developed a versatile in vitro model for studying the interactions between Pseudomonas aeruginosa and Staphylococcus aureus, two bacteria that commonly coexist in human infections. Using this model along with high-resolution, single-cell microscopy, we showed that P. aeruginosa and S. aureus form communities that are spatially structured at the micrometer scale, controlled in part by the production of an antimicrobial by P. aeruginosa. In addition, we provide evidence that this antimicrobial enhances S. aureus tolerance to an aminoglycoside antibiotic only during coculture.